Capillary electrophoresis coupled to chemometrics for analysis of carbon dots in nanoparticles mixtures. Issue 7 (30th January 2022) - Oliveira, Levi; Arroyave, Manuel; Pistonesi, Marcelo F.; Fragoso, Wallace; Springer, Valeria
Abstract: Since their discovery in 2004, carbon dots (CDs) have attracted attention due to their intrinsic physicochemical properties and the easy synthesis from simple precursors. However, quantification of CDs in mixtures of nanoparticles with similar sizes and surface functionality is still a challenging issue for research applications or regulatory purposes. In this work, CDs and silver nanoparticles were first synthesized under alkaline conditions by using glucose as precursor and capping agent, respectively. Mixtures of these nanoparticles were made at micromolar range, without purification, and then analyzed by CE–DAD, using an electrolyte solution composed of 20 mM sodium borate and 20 mM SDS at pH 8.5, in a total time of <15 min. The three‐way electrophoretic data were then decomposed by advanced chemometric models, parallel factor analysis and multivariate curve resolution–alternating least‐squares. The explained variances for both models were 95.8% (parallel factor analysis) and 85.3% (multivariate curve resolution–alternating least‐squares). In both cases, the quality of the results was verified by the root mean square standard deviation coefficient variation, which resulted lower than 5%, and no significant bias was observed at 95% of statistical confidence. Satisfactory prediction for CDs concentration was obtained with recovery values between 80.0% and 115%.